HIV-associated lipodystrophy: epidemiological analysis of a Plastic Surgery Service in Brazil - Secanho, Murilo Sgarbi [UNESP]; Neto, BALDUINO FERREIRA DE MENEZES [UNESP]; Carvalho, Laísa Brandão [UNESP]; Moragas, Weber Ribolli [UNESP]; Daronch, Oona Tomiê [UNESP]; Marcante, Renata Fernanda Ramos [UNESP]; Neto, Aristides Augusto Palhares [UNESP] (Thieme, 2023)
Introduction: Lipodystrophy is an important complication of HIV and has different clinical manifestations, such as lipoatrophy of the face, buttocks, and limbs and accumulation of fat in the abdominal and cervical regions. Lipodystrophy has aesthetic and psychosocial consequences, stigmatizing and affecting patients’ quality of life. The objective is to evaluate the epidemiology and treatments performed in patients treated at the HIV-related Lipodystrophy Outpatient Clinic at Hospital das Clínicas da Faculdade de Medicina de Botucatu. Method: The study was conducted retrospectively, with port analysis of patients treated between June 2012 and December 2019, at Hospital das Clínicas da Faculdade de Medicina de Botucatu, in Botucatu, SP, Brazil. Results: The medical records of 153 individuals were analyzed, 79 male and 74 female patients. The mean age was 45.6 years. The referrals came from 48 cities in four states. Caucasian patients accounted for 74.5% of the consultations. The complaint of facial lipodystrophy was reported by 52.9% of the patients. The most common invasive procedure was facial filling with polymethylmethacrylate (PMMA) in 62 patients. Gluteal implants were the most common surgery on six occasions. Conclusion: The data found show a higher proportion of female patients with complaints of lipodystrophy when compared to general data of patients with HIV. The white race was predominant, and the main complaint of lipodystrophy was facial atrophy. Facial filling with PMMA was the most common procedure.
Lipodistrofia associada ao HIV: análise epidemiológica de um Serviço de Cirurgia Plástica no Brasil
Keywords: Brazil; Epidemiology; HIV; HIV Seroprevalence; HIV-associated lipodystrophy syndrome; Reconstructive surgical procedures